POLYELECTROLYTE COMPLEX NANOPARTICLES OF SOLUBLE LIGNIN AND CHITOSAN AS INTERFACIAL MODIFIER (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
A water-soluble non-stoichiometric polyelectrolyte complex (LCP) was obtained as a result of the interaction of oppositely charged kraft lignin and high molecular chitosan by mixing their dilute water solutions. The sizes of the LCP nanoparticles were characterized by a bimodal distribution at pH 6, and their values were essentially smaller than the sizes of the chitosan particles. It was found that the LCP nanoparticles were characterized by remarkably lower values of surface tension at the air-water and the water-organic liquid interface in comparison with the initial biopolymers. With decreasing pH and increasing concentration of the LCP nanoparticles in the water solution, their adsorption ability at the interfaces was enhanced. The interface tension at the water-heptane interface changed non-linearly with increasing the polyelectrolyte complex concentration that was associated with the “saturation” effect. The dependence of the ability of the LPC nanoparticles to stabilize oil-in-water emulsion on pH values of the water phase was found.